2008
DOI: 10.1016/j.devcel.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Mediated Control of Cell Fate in Megakaryocyte-Erythrocyte Progenitors

Abstract: Lineage specification is a critical issue in developmental and regenerative biology. We hypothesized that microRNAs (miRNAs) are important participants in those processes and used the poorly understood regulation of megakaryocyte-erythrocyte progenitors (MEPs) in hematopoiesis as a model system. We report here that miR-150 modulates lineage fate in MEPs. Using a novel methodology capable of profiling miRNA expression in small numbers of primary cells, we identify miR-150 as preferentially expressed in the mega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
312
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(331 citation statements)
references
References 40 publications
15
312
4
Order By: Relevance
“…In this study, we identified miR-150 as a new regulator for MLL-associated leukemia, one of the most aggressive leukemias with a poor prognosis. miR-150 is a key miRNA involved in hematopoiesis via suppression of Myb and other potential target genes (6,7,13,14,45,46). Altered expression of crucial developmental regulators is often linked with diseases and cancer transformation, so it was not surprising to observe that altered expression of miR-150 was detected in multiple hematopoietic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified miR-150 as a new regulator for MLL-associated leukemia, one of the most aggressive leukemias with a poor prognosis. miR-150 is a key miRNA involved in hematopoiesis via suppression of Myb and other potential target genes (6,7,13,14,45,46). Altered expression of crucial developmental regulators is often linked with diseases and cancer transformation, so it was not surprising to observe that altered expression of miR-150 was detected in multiple hematopoietic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that miRNAs regulate hematopoiesis in both hematopoietic stem cells and committed progenitor cells [17][18][19][20][21][22][23][24][25]. Deregulated miRNA profiles have been reported in MPN patients during in vitro erythroid differentiation as well as in peripheral blood granulocytes, platelets, and reticulocytes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that these miRNAs downregulated mafB and HOXA-1, respectively, providing a mechanism for this biological effect. Using a novel method of miRNA profiling capable of generating a usable profile with as low as 10 ng of RNA, Lu et al 40 showed an overexpression of miR-150 in cells differentiated into the megakaryocytic lineage. Overexpression of miR-150 in megakaryocyte-erythrocyte progenitor cells led to a preferential differentiation toward the megakaryocytic lineage both in vitro and in vivo.…”
Section: Megakaryocyte Developmentmentioning
confidence: 99%